A gamified virtual learning environment for statistics learning - Tenório, Marcos Mincov (2022)
Virtual Learning Environments (VLE) provide a way for students to access and interact with learning experiences and assume the responsibility for their own learning, overcoming passive attitudes of listening and memorizing content. In other words, VLEs should be developed to provide teaching and learning environments that allows students to assume an active role in the development of their own knowledge and to increase their involvement. This work describes an experience of the application of a gamified VLE for the development of non- presential teaching and learning activities in the course of Statistics in a Management degree. To assess its impact, a quanti-qualitative methodology was used. Data was collected by four instruments: an online questionnaire with closed questions for students, an online questionnaire with open questions for students, a structured interview with the teacher, and instrumentation of the VLE to collect users’ actions on the platform. Results suggest that both teacher and students consider that it is beneficial to use the VLE because of its ubiquity and flexibility. Both students and the teacher consider that using VLE is beneficial, although the adaptation to gamification elements and concepts is still a challenge. The involvement of the teacher and the articulation between the VLE and the pedagogical approach is of the utmost importance to foster the students’ involvement in the teaching-learning process.